Using system dynamics to analyze the societal impacts of blockchain technology in milk supply chainsrefer. (May 2021) - Mangla, Sachin Kumar; Kazancoglu, Yigit; Ekinci, Esra; Liu, Mengqi; Özbiltekin, Melisa; Sezer, Muruvvet Deniz
Highlights: Map the milk supply chains to explore information flow among different members for higher traceability. Investigate the societal impacts of blockchain technology to build social sustainability. The systems theory in integration with system dynamics underpins this work. Collect data from an agricultural development cooperative in Turkey. Help achieve the SGDs of providing safe food, promoting good health and better well-being. Abstract: The integration of blockchain technologies in the food sector has significant social impacts. The objectives of this research are firstly, to map the milk supply chains to explore information flow among different members for higher traceability; secondly, to investigate the societal impacts of blockchain technology in a milk supply chain to build social sustainability. The systems theory in integration with system dynamics (SD) provides the necessary theoretical underpinning to this research. We collect data from an agricultural development cooperative founded to support dairy farmers in Turkey. This work evaluates the societal impacts of blockchain technology on farmers, the community and animals using parameters such as local embedding, rural development, decreasing food fraud, animal health and welfare, proximity to food markets, food security, educating and promoting people towards healthy eating, assisting food access and social acceptability for transparency. In the last 18 years, the cooperative has encouraged dairy farmers in the district to become partners with a resultant increase in milk production from 30 thousand tons in 2002 to 330 thousand tons in 2019. According to our findings, population growth of the country and adult population increases in the district, it is expected that by 2025 the number of partners will rise to approximately 2800. The increase in number of partners proves the network expansion. Furthermore, blockchain technology can be incorporated into the existing system so that transparent and end-to-end accurate tracking of the supply chain is made possible, while creating decentralized recording of transactions. Moreover, the critical traceability points of a milk supply chain are evaluated with the blockchain adoption. This will help achieve the sustainable development goals (SDGs) of providing safe food, promoting good health and better well-being for everyone.